Lunacy nach Geschichten von Edgar Allan Poe und Marquis de Sade - Poe, Edgar Allan; DeSade, Donatien Alphonse François (The Jan Švankmajer Collection, 2012)
The maestro of Czech animated surrealism, Jan Svankmajer, introduces "Lunacy", suggesting that it draws on Poe and de Sade. Fans of his shorts will be delighted by the animated interludes, as beef steaks, ox tongues and eyeballs get personal with one another. In the live-action story, orphan Jean (Pavel Liska) comes under the influence of the Marquis (Jan Triska), who, in between participating in black masses, orgies and ordering his own burial, suggests to Jean that he admits himself into the nearby asylum to cure his nightmare-inducing fear of madness. Since the institution follows the Marquis libertarian principles, the inmates have the run of the place to chaotic effect. The lunatics really take over the asylum, but would things really improve if the disciplinarian former regime returned to power? [www.amazon.co.uk]